Comparative effect of Trichoderma hamatum and host-specific Rhizobium species on growth of Vigna mungo - Rabia Badar, Shamim A. Qureshi (Journal of Applied Pharmaceutical Science)
The present study was designed to investigate the combine effect of Trichoderma hamatum and host-specific Rhizobium sp. of Vigna mungo on growth and biochemical parameters of same legume. The results proved that T.hamatum and host-specific Rhizobium sp are compatible with each other and their combine use was found effective not only in improving the growth parameters including lengths of roots & shoots and fresh biomass of experimental crop but also increasing the total chlorophyll, carbohydrate and crude protein contents as compared to control plants (p
Keywords: Trichoderma hamatum, Rhizobium species, Vigna mungo.